Ground temperature survey on Merapi Volcano - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRACT The measurements of the ground temperature survey on Mt. Minakami and this ground temperature survey is the second one. The technique of the measurements and the position of each measuring site are almost the same. The Gradient of the ground temperature is (-4.18+_ 1.75)C/km, While the Minakami was -6.1 C/km. The difference is insignificant wich means that there is no significant changes in the thermal activity of Merapi Volcano in both years.